2016
DOI: 10.1007/s10815-016-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations of CYP19A1 gene in Cumulus cells and its relevance to infertility in endometriosis

Abstract: Purpose The purpose of the present study was to investigate the epigenetic mechanisms responsible for the aberrant aromatase expression (CYP19A1) in Cumulus Cells (CCs) of infertile endometriosis patients. Method Cumulus cells were obtained from 24 infertile patients with and without endometriosis who underwent ovarian stimulation for intracytoplasmic sperm injection. Expression of CYP19A1 gene was quantified using Reverse Transcription Q-PCR. DNA methylation, histone modifications, and binding of Estrogen Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 60 publications
0
31
0
3
Order By: Relevance
“…Moreover, a study performed in cell culture showed that E 2 increased seladin-1 expression by activating estrogen response element (ERE) through ERα and protected cells against Aβ toxicity; however, these effects of E 2 disappeared when seladin-1 was silenced [33]. As it was shown that the aromatase gene also has 1/2ERE sites and that estrogen is one of the major inducers of aromatase [42], the decrease in hippocampal aromatase level after chronic inhibition of seladin-1 can be related to the decreased E 2 binding to the ERE on the aromatase gene, via ERα/β activation, thereby decreasing aromatase expression. The increasing effect of estrogen on aromatase expression was found to be dependent on its binding to ERβ and the consecutive activation of ERE on the aromatase gene in human ovarian cumulus cells [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study performed in cell culture showed that E 2 increased seladin-1 expression by activating estrogen response element (ERE) through ERα and protected cells against Aβ toxicity; however, these effects of E 2 disappeared when seladin-1 was silenced [33]. As it was shown that the aromatase gene also has 1/2ERE sites and that estrogen is one of the major inducers of aromatase [42], the decrease in hippocampal aromatase level after chronic inhibition of seladin-1 can be related to the decreased E 2 binding to the ERE on the aromatase gene, via ERα/β activation, thereby decreasing aromatase expression. The increasing effect of estrogen on aromatase expression was found to be dependent on its binding to ERβ and the consecutive activation of ERE on the aromatase gene in human ovarian cumulus cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…As it was shown that the aromatase gene also has 1/2ERE sites and that estrogen is one of the major inducers of aromatase [42], the decrease in hippocampal aromatase level after chronic inhibition of seladin-1 can be related to the decreased E 2 binding to the ERE on the aromatase gene, via ERα/β activation, thereby decreasing aromatase expression. The increasing effect of estrogen on aromatase expression was found to be dependent on its binding to ERβ and the consecutive activation of ERE on the aromatase gene in human ovarian cumulus cells [42]. Furthermore, several mechanisms underlying the effect of E 2 on aromatase expression have also been shown in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism in the CYP19A1 gene could alter an individual's susceptibility to endometriosis. Currently, many studies have indicated that CYP19A1 polymorphisms are associated with endometriosis development, and have revealed that these genetic polymorphisms are correlated with high levels of estrogen (Haiman et al, 2007;Allen et al, 2008;Hosseini et al, 2016). rs2899470 is located in the intron portion of the CYP19A1 gene, and is associated with levels of steroid hormones, such as testosterone and estrogen (Bulun et al, 2003;Barrett et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…E 2 /T ratio is an important indicator of aromatase activity, which is responsible for aromatization of androgens into estrogens (Jin et al, 2009). CYP19A1 gene polymorphism is associated with reduced aromatase activity, which can lead to the development of endometriosis (Wang et al, 2010;Zaree et al, 2015;Hosseini et al, 2016;Abu Hashim, 2016). While previous studies have investigated the association between CYP19A1 and risk of endometriosis, the results were inconsistent (Hur et al, 2007;Vietri et al, 2009;Yang et al, 2010;Szczepańska et al, 2013;Wang et al, 2012Wang et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Однако De Abreu et al сообщили, что НГЭ не оказывает существенного влияния на экспрессию гена CYP19A1 в клетках грану-лезы пациенток в протоколах ЭКО [64]. По дан-ным E. Hosseini et al [65], в клетках кумулю-са пациенток с НГЭ экспрессия гена CYP19A1 значительно ниже по сравнению с пациент-ками без НГЭ. Эти данные соответствуют ре-зультатам Barcelos et al о низком уровне мРНК ароматазы в кумулюсных клетках пациенток с НГЭ [66].…”
unclassified